Malaria Vector Bionomics: Countrywide Surveillance Study on Implications for Malaria Elimination in India - Manju Rahi; AK Mishra; Gyan Chand; RK Baharia; RK Hazara; SP Singh; Siraj Khan; U Sreehari; Divya Kamaraju; Gaurav Kumar; Sanjeev Kumar Gupta; Amit Sharma; et al. (JMIR Publications, 2024)
BackgroundThe biological characteristics of mosquito vectors vary, impacting their response to control measures. Thus, having up-to-date information on vector bionomics is essential to maintain the effectiveness of existing control strategies and tools, particularly as India aims for malaria elimination by 2030. ObjectiveThis study aims to assess the proportions of vector species resting indoors and outdoors, determine their preference for host biting/feeding, identify transmission sites, and evaluate the susceptibility of vectors to insecticides used in public health programs. MethodsMosquito collections were conducted in 13 districts across 8 Indian states from 2017 to 2020 using various methods to estimate their densities. Following morphological identification in the field, sibling species of Anopheles mosquitoes were identified molecularly using polymerase chain reaction (PCR)-specific alleles. Plasmodium falciparum and Plasmodium vivax infections in the vectors were detected using enzyme-linked immunosorbent assay (ELISA) and PCR assays. In addition, we assessed the insecticide susceptibility status of primary malaria vectors following the World Health Organization (WHO) protocol. ResultsAnopheles culicifacies, a primary malaria vector, was collected (with a man-hour density ranging from 3.1 to 15.9) from all states of India except those in the northeastern region. Anopheles fluviatilis, another primary vector, was collected from the states of Madhya Pradesh, Maharashtra, Karnataka, and Odisha. In Haryana and Karnataka, An. culicifacies sibling species A predominated, whereas species C and E were predominant in Madhya Pradesh and Maharashtra. An. culicifacies displayed mainly endophilic behavior across all states, except in Madhya Pradesh, where the proportion of semigravid and gravid mosquitoes was nearly half of that of unfed mosquitoes. The human blood index of An. culicifacies ranged from 0.001 to 0.220 across all study sites. The sporozoite rate of An. culicifacies ranged from 0.06 to 4.24, except in Madhya Pradesh, where none of the vector mosquitoes were found to be infected with the Plasmodium parasite. In the study area, An. culicifacies exhibited resistance to DDT (dichlorodiphenyltrichloroethane; with <39% mortality). Moreover, it showed resistance to malathion (with mortality rates ranging from 49% to 78%) in all districts except Angul in Odisha and Palwal in Haryana. In addition, resistance to deltamethrin was observed in districts of Maharashtra, Gujarat, Haryana, and Karnataka. ConclusionsOur study offers vital insights into the prevalence, resting behavior, and sibling species composition of malaria vectors in India. It is evident from our findings that resistance development in An. culicifacies, the primary vector, to synthetic pyrethroids is on the rise in the country. Furthermore, the results of our study suggest a potential change in the resting behavior of An. culicifacies in Madhya Pradesh, although further studies are required to confirm this shift definitively. These findings are essential for the development of effective vector control strategies in India, aligning with the goal of malaria elimination by 2030.